EPR spectroscopy studies of changes in erythrocyte membranes in patients with laryngeal cancer - Burlaka, Y.B.; Sukhoveev, O.V.; Grin, N.V.; Khilchevskyi, O.M.; Verevka, S.V. (Experimental Oncology, 2017)
Aim: To evaluate microviscosity and sorption capacity of erythrocyte membranes (SCEM) from patients with laryngeal cancer (LC). Materials and Methods: Samples from 35 patients with LC of stages II and III and 20 healthy volunteers were investigated by electron paramagnetic resonance with Bis(1-oxyl-2,2,6,6-tetramethylpiperidinyl-4)-ester of 5,7-dimethyladamantane-1,3-dicarbonic acid (AdTEMPO) probe. SCEM was evaluated by amount of unabsorbed methylene blue. Results: Microviscosity of erythrocyte membranes was determined by the effective rotational diffusion correlation times (τeff) and a decrease in radical spectrum signal intensity per hour. The most apparent decrease in mobility of the AdTEMPO in erythrocytes was observed prior to washing of erythrocytes with 0.9% NaCl for 5 min after probe insertion. The deceleration after 60 min was observed only in stage II LC. τeff was at control values after washing of erythrocytes of stage II LC 5 min after probe insertion and was significantly reduced in stage III LC in comparison to control. Radical spectrum signal intensity per hour in samples of stage II and III patients prior to and after washing of erythrocytes was on average 1.5-fold higher than that of control. SCEM in samples of stage II and III LC was found in 40 and 33% cases, respectively and was on average significantly reduced in comparison to control. Conclusions: The initial interaction of AdTEMPO with erythrocyte membranes of stage II and III LC patients is accompanied by an increase in τeff, indicating deceleration of probe rotation. τeff of the probe in membranes remains unchanged in 60 min, indicating changes in the structural organization of lipid bilayer and its associated proteins in particular. The similarity of SCEM for both studied groups reflects the pathological changes in function of erythrocyte membranes.